Urgency of Fulfilling Restitution Rights for Victims of Serious Assault Crimes (Decision Number 297/Pid.B/2023/PN Jkt.Sel) - Ramdes, Muhammad; Sugiharto, Sugiharto (Jurnal Hukum Khaira Ummah, 2025)
Indonesia as a country of law adheres to the Civil Law system, where the law is stated in systematically arranged laws and regulations. This legal system covers two main areas, namely public law and private law. Criminal law, which is included in public law, aims to regulate the interests of society in general. This law regulates the relationship between the state or society and individuals who violate legal provisions. This type of research is legal research conducted using the type of socio-legal research. Explaining that law can be studied and researched as a study of law that actually lives in society as a non-doctrinal and empirical study. 1. Fulfillment of the right to restitution for victims of serious assault crimes in Indonesia is a crucial aspect of the criminal law system that prioritizes restorative justice. However, until now there has been no comprehensive and explicit regulation governing the restitution mechanism specifically for serious assault cases. 2. The urgency of fulfilling the right to restitution is very high in the context of restorative justice that balances the punishment of the perpetrator and the recovery of the victim. The rights of victims are often neglected even though the perpetrator has been punished, whereas the losses experienced by victims of serious abuse are multidimensional, covering physical, psychological, social, and economic aspects. 3. Fulfillment of the right to restitution for victims of serious assault crimes is a concrete manifestation of the value of justice, as contained in the Pancasila Theory of Justice and the principle of the rule of law (rechtstaat).